If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+2(x-1)=5x+5(x-3)
We move all terms to the left:
8x+2(x-1)-(5x+5(x-3))=0
We multiply parentheses
8x+2x-(5x+5(x-3))-2=0
We calculate terms in parentheses: -(5x+5(x-3)), so:We add all the numbers together, and all the variables
5x+5(x-3)
We multiply parentheses
5x+5x-15
We add all the numbers together, and all the variables
10x-15
Back to the equation:
-(10x-15)
10x-(10x-15)-2=0
We get rid of parentheses
10x-10x+15-2=0
We add all the numbers together, and all the variables
13!=0
There is no solution for this equation
| 4x=8x^-1 | | 11(x+5)+3=-30 | | 6(6x+6)+8(6x+5)=123 | | 5=v/10+4 | | 54+2x+(x-2)=180 | | (5x+27)+(8x)=180 | | 2.3^x-1-8=10 | | (1÷2)+4m=3m+(5÷2) | | 18a-17=-161 | | x7-4=5 | | 47.7=9.6h+18.9 | | 4x-4=2(3x+1)-4x | | 2+5n=(n+2)-7 | | -0.71x+0.51x=4.6 | | 6x+2=13x-61 | | –8s=–9s−3 | | Y=5n2 | | (4x+24)=20 | | (20p/4)=5 | | 2(d+18)=-3(d+18) | | -7n-5=-110 | | 2(x+1)=x+x+2 | | 4x+13=2x+25 | | 1/2(4x+24)=20 | | Y=-5n | | 130=130-6t-16t^2 | | 11=v/5-10 | | .75x/4=22/4 | | -8x-13=5(8x-4)+7 | | 28=9k+10 | | 5x+x=11+13 | | 2(3+3)-1=2x+5 |